Implementation of Buzz Group Method To Increase Students' Confidence And Learning Outcomes of History Subject - Sulaihah Sulaihah; Bambang Soepeno; Mohamad Naim (History Education, University of Jember, 2018)
Learning History requires the learnes to have the ability to critical thinking, responsive, and argumentative in learn the values about the life of the past society and its development into the future. These abilities will be realized if there is a high confidence in learnes' self. Confidence is important to learners because it can provide awareness of the changes and values contained in every historical event. The purpose of this study was to analyze the increased confidence and learning outcomes of students by applying the learning method Buzz Group students of class XI IPS 1 SMAN 1 Jember. The subject of this study were 30 students of XI IPS 1 SMAN 1 Jember. The results showed that there was an increase in confidence and learning outcomes at each cycle. 5 indicators confidence can be inferred from cycle 1 to cycle 2 increase 6,52%. Classically the scores of the students' learning confidence in the first cycle is 63,73% and 70,25% in the second cycle. In the third cycle experienced an increased of 8,01% to 78,26%. The scores of the students' learning outcomes classically increase to 10%. Classically the scores of the students' learning outcomes in the first cycle is 73,33% and 83,33% in the second cycle. In the third cycle increased 3,33% to 86,67%. The conclusion of this research was that the application of the learning method Buzz Group can increase students' confidence and learning outcomes in History of class XI IPS 1 SMAN 1 Jember academic year 2016/2017. Keyword: Buzz Group, Confidence, Learning outcomes of the history subject